Implementasi Metode Waterfall Pada Sistem Informasi Perpustakaan Berbasis Web (Studi Kasus SDN Tegalangus) - Muhammad Nur Alamsyah; Ratih Yulia Hayuningtyas (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
School libraries must be managed properly in order to provide good service to all visitors. The library is one of the facilities provided by the school to support teaching and learning activities for school students. In addition, the school library is an information center that can increase students' knowledge and insight. The SDN Tegalgus library in library operational activities such as borrowing and returning still uses manual methods so it takes a long time to find books and officers still have difficulty managing borrowing and returning data because all transactions are recorded in books so errors often occur. With this problem, a review was carried out by SDN Tegalangus which considered less effective for library operational activities. SDN Tegalangus requires an information system that can carry out library activities by applying information technology. Information systems have a role in various aspects, one of which is the library can provide benefits for visitors and officers. In this study, a website-based library information system will be made by applying the waterfall method which can overcome the problems that exist in the Tegalangus Elementary School library so that the information in the library is faster, more precise and accurate for all library users.